Socio-Environmental Survey and Sustainable Management Planning of a Forest Hamlet Proximate to Mahananda Wildlife Sanctuary in the Eastern Himalayas, India - Bhattacharya, Sayan (Sumatra Journal of Disaster, Geography and Geography Education, 2020)
The Himalayas have significant impact on the climate and biodiversity of the Indian Subcontinent. Many hamlets are situated in the Eastern Himalayas and some of them are proximate to the forest areas. Latpanchar (26.7083 N, 88.4268 E) is one of the emerging tourist destinations of the Eastern Himalayas, situated at an altitude of 4200 feet, nestled on the highest part of Mahananda wildlife sanctuary. Latpanchar being home to over 200 diverse varieties of bird species including Rufous Necked Hornbill is a very attractive destination for bird watchers. As a result, the hamlet has developed as an attractive ecotourism destination. Most of the inhabitants of the village are associated with Latpanchar Cinchona Plantation, which was established in 1943. The present study focuses on the physical and cultural environment of the forest and mountain areas in Latpanchar. The survey work integrates the perspectives of social ecology, ecosystem services and sustainable development. Primary data were collected using a mixed-methods approach, collecting background baseline information, scheduling interviews with members of the local villages and field observations. Focus was given on demography, agriculture, livestock management, water management, education, health, waste management, disaster management, biodiversity, ecosystem services, conservation initiatives and human animal conflict. Photographic documentation accompanied every phase of the survey. Policy proposals for sustainable development of the hamlet were discussed for conserving the biodiversity and socio-environmental condition of the village. Extensive study is needed in other mountain areas of the Eastern Himalayas to explore the socio-ecological conditions in the context of climate change.